The Influence of Self-Directed Learning Assisted by Modules on Mathematical Literacy in Terms of Students' Learning Independence - Man, Youlanda L; Hidayah, Isti; Nino Adhi, Nuriana Rachmani Dewi (Al-Khawarizmi, 2023)
This research aims to see the effect of self-directed learning assisted by modules on students' mathematical literacy based on students' learning independence. The experimental design used in this research is factorial experimental. The population in this study were all tenth-grade students at MA Plus Walisongo Kotabumi. The samples in this study were students of class X MIA 1 as the experimental and students of class X MIA 2 as the control class for each class of 32 students. The data were subjected to analysis using a two-way ANOVA test. The findings in this research are: 1) there is an influence of self-directed learning assisted by modules on students' mathematical literacy; 2) there is an influence of high, medium, and low learning independence categories on students' mathematical literacy; 3) there is an interaction between self-directed learning assisted by modules and the category of independent learning on students' mathematical literacy.